Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/jmri.25088
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of tibial subchondral bone: Texture analysis outperforms conventional trabecular microarchitecture analysis

Abstract: PURPOSETo compare two different methods of quantitative assessment of tibial subchondral bone in osteoarthritis (OA): statistical texture analysis (sTA) and trabecular microarchitecture analysis (tMA). METHODSAsymptomatic controls aged ͮͬ-ͯͬ (n=ͭͬ), patients aged Ͱͬ-ͱͬ with chronic knee pain but without established OA (n=ͭͬ) and patients aged ͱͱ-ʹͱ with advanced OA scheduled for knee replacement (n=ͭͬ) underwent knee MR imaging at ͯT with a ͯD gradient echo (GRE) sequence to allow sTA and tMA.tMA and sTA fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…While multiple prior research studies have investigated the use of a texture analysis applied to MR images the underlying influence of MRI scan parameters on texture analysis features are not entirely understood. Furthermore, despite the increasing use of texture analysis in the field of radiology, a fundamental understanding of the histopathologic and biologic correlation between tissue and texture analysis features remains in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…While multiple prior research studies have investigated the use of a texture analysis applied to MR images the underlying influence of MRI scan parameters on texture analysis features are not entirely understood. Furthermore, despite the increasing use of texture analysis in the field of radiology, a fundamental understanding of the histopathologic and biologic correlation between tissue and texture analysis features remains in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that improved system performance in the discrimination task will translate also to improved performance in the threshold‐based quantitative measurements. A potentially more challenging extension of this work might involve predicting the performance of a texture classification algorithm applied to trabecular regions . The investigation of textural biomarkers of bone quality is still in early stages and there is no consensus yet as to which of the textural features are best suited for diagnostic applications.…”
Section: Discussionmentioning
confidence: 99%
“…A potentially more challenging extension of this work might involve predicting the performance of a texture classification algorithm applied to trabecular regions. [77][78][79][80] The investigation of textural biomarkers of bone quality is still in early stages and there is no consensus yet as to which of the textural features are best suited for diagnostic applications. For some features, such as those based on the gray-level co-occurrence matrix, 81 improved conspicuity of fine trabecular detail may improve the sensitivity of classification.…”
Section: Discussionmentioning
confidence: 99%
“…Microarchitecture was a stronger predictor of bone strength than trabecular texture (37). MacKay et al (38) assessed tibial subchondral bone in patients with osteoarthritis and found that trabecular texture, but not microarchitecture parameters, helped accurately classify patients with and patients without osteoarthritis.…”
Section: Musculoskeletal Imaging: Trabecular Ct Texture Analysis In Amentioning
confidence: 99%